Pengembangan Aplikasi Rental Mobil Berbasis Web di Rental Angelita Rentcar dengan Model Spiral - Juwono Juwono; Rizal Diantoro; Indah Purwati; Fariduddin Octa Aryanto; Yulianti Yulianti; Sri Mulyati (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Angelita Rentcar is a car rental application that has been developed and operating since 2005. Angelita Rentcar provides several services related to car rental. On the website page, the car selection is based on the type, price, and suggestions for each selected vehicle. Initially, the promotion process was carried out by giving each other information through fellow consumers and placing advertisements in the mass media. But this method is less successful because information about the type of car being rented cannot be displayed completely and clearly by the rental provider. So far, the transaction process has only been done by telephone or coming to the rental company. Problems occur when renting by telephone because it takes time to get information about the vehicle to be used, and the car rental transaction process is quite long because it still uses a desktop application. Telephone transactions also sometimes disappoint consumers because the cars they get are not the ones ordered. This is a problem that must be overcome, therefore it is necessary to build a car rental application called Angelita Rentcar. This application is web-based to be integrated for all divisions. This application development uses a spiral model that prioritizes feedback from consumers. In this application, the payment process and detailed car information can be done more easily and efficiently by consumers. Security of data and transactions will be guaranteed. So with this web-based car rental information system called Angelita Rentcar, promotions, car rental systems and customer satisfaction can increase, information is more precise and faster in helping company performance and customer satisfaction.